Solidarity, Media, and the Limits of Postcapitalist Theory. (April 2015) - Popp, Richard K.
This essay critically examines the postcapitalist characteristics of civil sphere theory (CST) and their implications for locating media in large-scale processes of social change. Providing a case study of U.S. media between the 1930s and 1980s, the essay argues that because CST treats media as free-floating images, rather than cultural industries and consumer practices, it is unable to account for a wide range of episodes in the making and unmaking of solidarity, including the Depression era's specter of social unraveling, the suburban dismantling of the industrial city's public amusement culture, and the emergence of a post-1960s New Right lens on media. The essay suggests that CST's approach to solidarity should be modified to account for media's deep embeddedness in the culture of capitalism. This would include recognizing that popular visions of community take shape within, and in response to, an economic culture uniquely prone to change. It would also include recognizing that messages and moments of solidarity are always experienced within built environments shaped by capital flows.